Anti‐obesity effect of feeding probiotic dahi containing Lactobacillus casei NCDC 19 in high fat diet‐induced obese mice. (25th August 2014) - Rather, Sarver A; Pothuraju, Ramesh; Sharma, Raj Kumar; De, Sachinandan; Mir, Nazir A; Jangra, Surender
<x xml:space="preserve">Abstract</x> Nowadays, studies about the anti‐obesity potential of probiotics are of growing interest. Lactobacilli are one of the well‐studied probiotics owing to their preventing effect on metabolic disorders. This study was undertaken to access the anti‐obesity effect of probiotic dahi containing Lactobacillus casei NCDC 19 on C57BL/6 mice. Feeding of probiotic dahi showed reduce body weight gain and epididymal fat weights. Moreover, blood glucose, plasma lipids and expression level of leptin were reduced and caecal bifidobacteria counts and adiponectin expression levels were significantly increased. It can be concluded that feeding of probiotic dahi containing L. casei NCDC 19 showed potential anti‐obesity effects.